2013
DOI: 10.1016/j.diagmicrobio.2012.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary infection due to Pseudozyma aphidis in a patient with burkitt lymphoma: first case report

Abstract: Fungal infections are being increasingly reported in patients with malignancies. Pseudozyma aphidis is an opportunistic yeast usually isolated from plants and rarely from human samples. In this study, we report the first case of pulmonary infection due to P. aphidis in a Burkitt lymphoma patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 13 publications
2
20
0
Order By: Relevance
“…However, on CHROMagar Candida, our isolates developed creamcolored colonies, in contrast with the findings of Prakash et al (14), and could not be identified using an API 20 AUX system. Due to this, sequencing of ITS and/or D1/D2 domains was necessary for proper identification, in agreement with the literature (8,(11)(12)(13)(14)(15). Also, isolates could not be identified by MALDI-TOF.…”
supporting
confidence: 70%
See 3 more Smart Citations
“…However, on CHROMagar Candida, our isolates developed creamcolored colonies, in contrast with the findings of Prakash et al (14), and could not be identified using an API 20 AUX system. Due to this, sequencing of ITS and/or D1/D2 domains was necessary for proper identification, in agreement with the literature (8,(11)(12)(13)(14)(15). Also, isolates could not be identified by MALDI-TOF.…”
supporting
confidence: 70%
“…Unfortunately, we have no record of the patient dietary history. It is also worth noting that, as in the present work, three of the four cases in which P. aphidis were isolated involved pediatric patients (11,(13)(14)(15).…”
supporting
confidence: 69%
See 2 more Smart Citations
“…infection most often presents with fungaemia. Moreover, deep-seated focal infections including brain abscess [125] and pleural cavity have been reported [124]. Finally, a single case of a mycetoma due to co-infection with Nocardia after traumatic inoculation in an Asian farmer has been described [126].…”
Section: Risk Factors/clinical Presentationmentioning
confidence: 99%